Isolasi Senyawa Flavonoid dari Ekstrak Metanol Daun Katuk (Sauropus androgynus (L.) Merr), Euphorbiaceae - RATNA DJAMIL; SARAH ZAIDAN (JURNAL ILMU KEFARMASIAN INDONESIA, 2016)
Katuk (Sauropus androgyrus (L.) Merr) is one of the plants used for medicinal purposes. It has been carried out the research to isolate and to identify flavonoid compounds in the methanol extract of katuk leaves using paper chromatography and spectrophotometry ultraviolet-visible. The results demonstrated that light spectrum of uv-visible in the presence of a reagent gave an isolate NB-3 which was a compound suspected of flavonol with OH group in positions 5,7,4 ‘and o-di OH groups in the position of the A-ring (6,7 or 7,8) whrereas NB-4 isolate was suspected as flavonoids with OH groups at 5.7 and the prenil groups in position 6, methylation or glycosylation at OH group in a position 3 and o-di OH groupsin position of the a-ring (6,7 or 7,8).